2011
DOI: 10.1007/s11748-011-0841-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low-dose landiolol, an ultrashort-acting β-blocker, on postoperative atrial fibrillation in patients undergoing pulmonary resection for lung cancer

Abstract: Low-dose landiolol can be effective quickly and used safely in patients who develop atrial fibrillation after pulmonary resection for lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…Recently, more and more results showing the efficacy of landiolol in terminating postoperative atrial fibrillation [8,17,18]. Beta blockers reduce the rate of sudden death, and research has pointed to a beneficial effect in patients with ventricular tachyarrhythmias [19].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more results showing the efficacy of landiolol in terminating postoperative atrial fibrillation [8,17,18]. Beta blockers reduce the rate of sudden death, and research has pointed to a beneficial effect in patients with ventricular tachyarrhythmias [19].…”
Section: Discussionmentioning
confidence: 99%
“…Landiolol has also been shown to be well tolerated in the critically ill for its limited negative inotropic effect and minimal impact on blood pressure [99][100][101]. The use of low doses (5-10 mcg kg -1 min -1 ) of landiolol is usually sufficient for the cardioversion of AF compared to controls.…”
Section: Beta-blockersmentioning
confidence: 99%
“…In lung cancer, AF is most frequently seen during thoracic surgery, especially pulmonary resection [20]. Numerous studies in patients undergoing lung cancer surgery reported incidences of AF ranging 5.6%-23% [16,[21][22][23]. Previously, thoracic surgery was demonstrated to be an important risk factor for the occurrence of AF [24].…”
Section: Postoperative Af (Poaf) In Cancermentioning
confidence: 99%